Intra and extraarticular localized pigmented villonodular synovitis - Juneja, Johney; Choubisa, Raghvendra; Sen, Ramesh; Mehra, A. K.; Aggarwal, Basant; Sharma, Krishan Kumar (International Journal of Research in Orthopaedics, 2021)
A 28 year old woman had a history of knee trauma and presented with unilateral knee acute swelling and pain symptoms with sudden onset, which was there from last 2 years. She had been treated for seronegative rheumatoid patient for 1 year. Recent expansion of the LPVNS (localized pigmented villonodular synovitis) caused the development of a tender palpable soft tissue mass in the anterolateral aspect of the knee and acute reduced mobility. Preoperative magnetic resonance imaging of the knee revealed the presence of only the soft tissue mass and mild degenerative changes. Open synovectomy was performed successfully to excise the mass. Intraoperatively, macroscopic features of the bright brown inflamed synovium suggested LPVNS, which was confirmed histopathologically. Postoperatively, the symptoms of limited mobility and pain were appreciably relieved. Recurrence was not observed during the clinical follow up at 1, 6 or 18 months after surgery. Here, we reported the unique case of localized pigmented villonodular synovitis of the knee in a misdiagnosed patient with intra and extraarticular lesion, which might be attributed to the history of knee trauma and the focal defect of the lateral patellar retinaculum. Open synovectomy effectively relieved the symptoms of limited mobility and pain and no recurrence was observed prior to 18 months postoperatively. To reduce misdiagnosis, MRI examinations are recommended for all patients suspected of having PVNS, including those who have a history of hyperuricemia.